Bidirectional association between disturbed sleep and neuropathic pain symptoms: a prospective cohort study in post-total joint replacement participants - Stocks, Joanne; Tang, Nicole K.Y.; Walsh, David A.; Warner, Sophie C.; Harvey, Hollie; Jenkins, Wendy; Abhishek, Abhishek; Doherty, Michael; Valdes, Ana M. (Dove Medical Press, 2017)
Disturbed sleep is strongly correlated with chronic pain. The aim of this study was to examine the association between sleep disturbance and incident joint pain focusing on neuropathic pain-like symptoms. 423 individuals who had undergone total joint replacement (TJR) for osteoarthritis (OA) were assessed 3.6 years post-surgery, using the Medical Outcomes Survey sleep subscale, the WOMAC and PainDETECT instruments, and again 5.9 years post-TJR. Cox hazards ratios (HR) and 95% confidence intervals (CIs) were computed adjusting for age, BMI, sex, use of hypnotic and analgesic medication. The presence of neuropathic pain symptoms predicted incidence of disturbed sleep after adjustment for covariates and pain severity (aHR 2.01, 95% CI: 1.00-4.10 p<0.05). There was no association between joint pain and incidence of disturbed sleep when individuals with neuropathic pain symptoms at baseline visit were excluded (aHR 1.11, 95% CI: 0.47-2.67). Disturbed sleep at baseline predicted incident neuropathic joint pain symptoms (aHR 2.75, 95% CI: 1.21-6.26; p<0.016) but had no effect on incidence of joint pain when all types of pain were considered together (aHR 0.63, 95%CI: 0.30-1.39). These data suggest a causal bidirectional link between sleep disturbance and joint pain with neuropathic features, but not with other types of joint pain.